A Preliminary Trial in the Efficacy of Yokukansankachimpihange on REM Sleep Behavior Disorder in Dementia With Lewy Bodies - Manabe, Yuta (Frontiers in Nutrition, 2020)
Background: Clonazepam (CNZP) is effective in approximately 90% of patients with rapid eye movement sleep behavior disorder (RBD), but has risks of oversedation, muscular relaxation, and adverse effects on cognitive function when used to treat RBD associated with dementia with Lewy bodies (DLB). Yokukansankachimpihange (YKSCH), a traditional herbal medicine, decreases sleep latency and increases sleep stage 2, like benzodiazepines (BZPs), but does not cause adverse events such as oversedation, muscular relaxation, or adverse effects on cognitive function. Given these pharmacological properties, YKSCH was studied as a potential alternative to CNZP. Methods: Of patients who were diagnosed with DLB according to the criteria for the clinical diagnosis of DLB established by the Consortium on Dementia with Lewy Bodies (CDLB) in 2017, 13 consecutive patients with the cut-off score (5 points) or more in an REM sleep behavior disorder screening questionnaire and polysomnographic evidence of REM without atonia were observed using the Neuropsychiatric Inventory (NPI)-night time behavior disturbance, visual analog scale (VAS)-frequency, and VAS-severity as the co-primary endpoints. Data from 11 patients who completed the study were statistically analyzed. Results: Statistically significant improvements were observed in the NPI-night time behavior disturbance, VAS-frequency, and VAS-severity. No notable adverse events were reported. Conclusion: The results indicated that YKSCH, which does not cause oversedation, muscular relaxation, or adverse effects on cognitive function, may provide a new therapeutic option for RBD associated with DLB as an alternative to CNZP.